PENTINGNYA PENINGKATAN SOFT SKILL DI ERA DISRUPSI BAGI PENDIDIK DAN TENAGA KEPENDIDIKAN SMA RK BINTANG TIMUR YPK. ST. LAURENSIUS PEMATANG SIANTAR - Elvie Maria; Victor Victor; Andriasan Sudarso (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Disruption era is marked by major and fundamental changes in all areas of life, due to disruptions which change the system of social life in general, massive innovation and change occur, this is what has changed various systems from old to new patterns. Efforts to deal with the era of disruption are by improving the quality of human resources, digital transformation, and not stopping to innovate. Realized it was of disruption, as one of the best schools in Pematangsiantar, SMA RK Bintang Timur, YPK St. Laurensius continues to strive to maintain its existence, so one of the strategies adopted is to hold seminars to improve the quality of its human resources, namely educators and educational staff in this institution are called Teachers and Employees with the aim of understanding and realizing the importance of improving the soft skills required in the era of disruption, in order to improve individual and organizational performance.